Gothic Elements in The Picture of Dorian Gray and The Strange Case of Dr Jekyll and Mr Hyde - Heltová, Edita (Univerzita Pardubice, 2013)
The aim of this paper is to analyze Gothic elements in The Picture of Dorian Gray by Oscar Wilde and The Strange Case of Dr Jekyll and Mr Hyde by Robert Louis Stevenson. The introductory chapter provides a thorough insight into the development of the English Gothic novel since its origin in the eighteenth century until the end of the Victorian era. The theoretical part also examines how Gothic elements changed and transformed in the course of time and why the motif of duality became the main element of Gothic novels written in the last two decades of the nineteenth century. The following part is based on the analysis and comparison of the Gothic elements appearing in the two selected works, focusing on the motif of duality, London as a Gothicized space and other objects of fear and horror.
Gotické prvky v dílech Obraz Doriana Graye a Podivný případ doktora Jekylla a pana Hyda
Keywords: Picture of Dorian Gray; Strange Case of Dr Jekyll and Mr Hyde; Wilde, Oscar; Stevenson, Robert Louis; Gothic elements; Gothic novel; duality; Victorian era; Obraz Doriana Graye; Podivný případ doktora Jekylla a pana Hyda; gotické prvky; gotický román; dualita; viktoriánské období